Single-institution Experience of Unrelated Cord Blood Transplantation for Primary Immunodeficiency. Issue 3 (April 2015) - Chang, Tsung-Yun; Jaing, Tang-Her; Lee, Wei-I; Chen, Shih-Hsiang; Yang, Chao-Ping; Hung, Iou-Jih
<x xml:space="preserve">Abstract</x> Pediatric patients with primary immunodeficiencies (PID) constitute life-threatening medical emergencies. In the absence of an HLA-identical hematopoietic stem cell donor, unrelated donor cord blood transplantation (CBT) is another treatment option. There are little data regarding the outcome of unrelated CBT for PID in Taiwan. We report the results of CBT performed in 8 patients with PID between 2004 and 2013 at Chang Gung Memorial Hospital. The cases included severe combined immunodeficiency (n=4), chronic granulomatous disease (n=2), Wiskott-Aldrich syndrome (n=1), and T-cell immunodeficiency (n=1). Median follow-up time was 73 months. Most UCB recipients received a myeloablative conditioning regimen. There were 7 boys and 1 girl with a median age of 2.5 months at diagnosis (range, antenatal to 17 mo). Median age at transplant was 5.5 months (range, 2 to 74 mo). All but 1 patients engrafted at a median time of 14 days. One developed significant grade III graft-versus-host disease after transplant. Our data show that unrelated CBT in PID is possible. However, no definite conclusions can be drawn from this small number of patients, and more studies are needed to further investigate and confirm these findings.